THE EFFECT OF COMPETENCY AND INNOVATION ON THE PERFORMANCE OF MSME ACTORS WITH CREATIVITY AS AN INTERVENING VARIABLE IN MICRO-ENTERPRISES IN KELAMBIR VILLAGE, LIMA KEBUN - Kiki Farida Ferine; Firmansyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of competence and innovation on the performance of Micro, Small, and Medium Enterprises (MSMEs) with creativity as an intervening variable in micro-enterprises in Kelambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency. The research approach used is quantitative with a causal associative research type. The study population was all active MSMEs in Kelambir Lima Kebun Village, totaling 83 people, and was also sampled using a saturated sampling technique , so that the entire population was studied. Primary data were collected through a questionnaire with a five-point Likert scale, while secondary data were obtained from official village documents, reports from the Cooperative and MSME Office, and supporting literature. Data analysis was carried out using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test direct and indirect relationships between variables. The results of the study indicate that (1) competence has a positive and significant effect on the performance of MSMEs, (2) innovation has a positive and significant effect on performance, (3) competence has a positive and significant effect on creativity, (4) innovation has a positive and significant effect on creativity, and (5) creativity has a positive and significant effect on performance. In addition, creativity is proven to partially mediate the influence of competence and innovation on the performance of MSMEs. These findings emphasize the importance of improving competence and innovation as primary factors in optimizing performance, with creativity as an additional driver that strengthens the success of micro-enterprises.